Crack detection in dielectric structures by a linear sampling approach. (1st September 2010) - Bozza, G.; Brignone, M.; Pastorino, M.; Piana, M.; , A. Randazzo
In this paper, a new approach for the detection of cracks and defects inside dielectric structures is presented. The proposed algorithm is based on the Linear Sampling Method (LSM), which is a technique able to find the external shape of unknown objects starting from far-field measurements of the scattered electric field. In particular, in this contribution, the efficient No-Sampling LSM is modified to provide a reconstruction of the positions and shapes of defects located inside a known structure. This task is accomplished by inserting the Green's function of the unperturbed object into the far-field equation. The effectiveness of the approach is assessed by means of numerical simulations.